2013
DOI: 10.1016/j.celrep.2013.04.024
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide Map of CTCF Multivalency Redefines the CTCF Code

Abstract: SUMMARY The “CTCF code” hypothesis posits that CTCF pleiotropic functions are driven by recognition of diverse sequences through combinatorial use of its 11 zinc fingers (ZFs). This model, however, is supported by in vitro binding studies of a limited number of sequences. To study CTCF multivalency in vivo, we define ZF binding requirements at ~50,000 genomic sites in primary lymphocytes. We find that CTCF reads sequence diversity through ZF clustering. ZFs 4–7 anchor CTCF to ~80% of targets containing the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
387
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(431 citation statements)
references
References 63 publications
40
387
2
2
Order By: Relevance
“…S9), resulting in H3K9me2 domain disruption and spreading. A recent work has indicated a remarkable diversity of DNA sequence motifs for CTCF binding, with specific motifs associated with strength of CTCF binding (33). Intriguingly, we identified a motif at the weak CTCF-binding sites that was previously shown to be associated with weaker CTCF binding (33).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…S9), resulting in H3K9me2 domain disruption and spreading. A recent work has indicated a remarkable diversity of DNA sequence motifs for CTCF binding, with specific motifs associated with strength of CTCF binding (33). Intriguingly, we identified a motif at the weak CTCF-binding sites that was previously shown to be associated with weaker CTCF binding (33).…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, de novo motif discovery analysis (SI Materials and Methods) at disrupted CTCF peaks indicated the presence of a CTCF motif that was previously characterized to be associated with weaker CTCF-binding compared with the canonical CTCF site (Fig. 4D) (33). Furthermore, evaluating the levels of H3K9me2 at the lost and retained CTCF sites demonstrated that the lost CTCF sites do indeed have enrichment of H3K9me2 relative to retained sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is a precedent for zinc finger proteins directing CTCF to target sites. Recently it was demonstrated that sequences flanking core CTCF binding elements influence CTCF binding in vivo (22). Cooperative loading of CTCF and protein binding partners onto chromatin may explain this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, the intriguing observation was made that depletion of the CTCF partner centrosome-associated zinc finger protein (CP190) resulted in a reduced pool of CTCF associated with chromatin (21). An elegant study mapping the sequence specificity of the 11 zinc finger proteins of CTCF found that flanking sequences could influence CTCF binding through an unknown mechanism (22). These flanking sequences do not target CP190 because there is no human homolog.…”
mentioning
confidence: 99%
“…The effect of mediator depletion on topological domains and other chromatin interactions remains to be explored more fully. Of interest, CTCF occupancy depends not only on the combinatorial binding of its 11 zinc fingers that recognize specific DNA elements but also on extrinsic factors, including the DNA sequence, that either stabilize or destabilize CTCF binding (13). Evaluation of the influence of different sequence motifs on the stability of CTCF-mediated loops will help further the characterization of topological domains.…”
Section: Dna Interactions Within Chromosomal Territoriesmentioning
confidence: 99%